Evaluation of FSH Receptor Gene Polymorphisms among infertile women and its correlation with Ovarian Reserve Markers and fertility outcomes: A Prospective Observational Study from Northern India - Bahadur, Anupama; Naithani, Manisha; Dobhal, Shivashish; Rajandran, Priyanka; Singh, Gupchee; Rao, Shalinee; Sharma, Jai Bhagwan (Indian Journal of Community Health, 2025)
Background: Genetic polymorphisms in the Follicle-Stimulating Hormone Receptor (FSHR) gene may influence ovarian response in women undergoing controlled ovarian stimulation, but their relevance in infertile women undergoing ovulation induction remains uncertain. Aims & Objectives: To assess the association of FSHR polymorphisms Thr307Ala (rs6165) and Asn680Ser (rs6166) with ovarian reserve markers and fertility outcomes in infertile women undergoing ovulation induction. Methodology: This prospective observational study, conducted from August 2021 to May 2025, included 82 infertile women and 25 fertile controls. All participants underwent Day 2–5 (AMH, FSH, LH, E2), Antral Follicle Count (AFC), and FSHR genotyping using PCR-RFLP. Letrozole was used for ovulation induction for up to four cycles. Results: Genotype and allele distributions for both polymorphisms did not differ significantly between infertile and fertile women. All genotype frequencies conformed to Hardy–Weinberg equilibrium except Asn680Ser (rs6166) in controls. Ovarian reserve markers were comparable across genotypes, except for higher AMH in fertile controls with the AA genotype of Thr307Ala (p = 0.017) and significantly higher AFC among infertile women (p = 0.0001). Letrozole-induced ovulation and pregnancy rates (12%). Conclusion: FSHR polymorphisms Thr307Ala and Asn680Ser do not significantly affect ovarian reserve parameters or clinical outcomes in infertile women undergoing ovulation induction, indicating limited predictive value in this setting.